MORPHOMETRIC CHARACTERISTICS OF THE JEJUNUM WALL IN ACUTE ABDOMINAL ASEPTIC INFLAMMATION IN RATS - Shepitko, K.V.; Сhaikovskiy Y.B. (World of Medicine and Biology, 2014)
The investigation has been conducted on 60 adult male rats. The dynamics of changes has been demonstrated in morphometric parameters of the total thickness of the wall, thickness of the mucosa, submucosa, muscular and serous shells of the jejunum, with a single intraperitoneal injection of 5 mg λ - caragenan (Sigma - USA) which has been dissolved in 1 ml of saline per animal. It has been estimated, that morphometric parameters have not significantly distinguished between the indices of intact group and control groups of animals. In inflammation the indicators of total wall thickness, the thickness of the mucosa and submucosa react by increasing of their indices on the 10-14 days of experiment to the maximum that indicates to the manifestation of degenerative processes with atrophy of the jejunum.